1975
DOI: 10.1073/pnas.72.8.3144
|View full text |Cite
|
Sign up to set email alerts
|

Surface ruffles as markers for studies of cell transformation by Rous sarcoma virus.

Abstract: Confluent chick embryo fibroblasts infected with the Ts68 mutant of Rous sarcoma virus were examined by scanning electron microscopy at the permissive (360) and nonpermissive (410) temperatures for transformation. Infected cells shifted from 410 to 360 undergo a change in shape from elongated to rounded. This process is preceded by the appearance of surface ruffles on the cell. These surface ruffles are not observed on cells maintained at 410, appear as early as 0.5 hr after a shift to 360, and are common on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(26 citation statements)
references
References 8 publications
(9 reference statements)
3
23
0
Order By: Relevance
“…These results indicate the presence of clathrin heavy chain phosphatase activity in the membranebound fraction. Transformation by RSV is known to cause phenotypic changes, in part through alterations in cytoskeletal organization (Ambros et al, 1975). We compared the distribution of clathrin in normal and transformed cells by immunofluorescent staining using either of two anti-clathrin light chain antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate the presence of clathrin heavy chain phosphatase activity in the membranebound fraction. Transformation by RSV is known to cause phenotypic changes, in part through alterations in cytoskeletal organization (Ambros et al, 1975). We compared the distribution of clathrin in normal and transformed cells by immunofluorescent staining using either of two anti-clathrin light chain antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…Morphological alterations of the cell surface and cytoskeleton are among the earliest manifestations of the src gene product (Ambros et al, 1975;Boschek et al, 1981). Among the cell surface changes, it has been observed that a number of receptors, including those for epidermal growth factor and thrombin, are cleared from the surface by endocytic events that may be altered by pp60 ~-s~ (Decker, 1983;Cooper et al, 1983;Zetter et al, 1977).…”
mentioning
confidence: 99%
“…The earliest phenotypic manifestation of src activation is membrane ruffling along the cell margins when fibroblasts infected with a temperature-sensitive v-src mutant are shifted from the restrictive to permissive temperature (45). Activation of a temperature-sensitive v-src mutant also leads to association of activated v-src with the detergent-insoluble cytoskeleton, and is accompanied by changes in both actin organization and the distribution of the actin-binding proteins ␣-actinin and vinculin (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…These types of motility may be expressed after several types of biological stimulation. For example, oncogenes (1)(2)(3)(4), hormones (5), and various growth factors (6)(7) have been demonstrated to induce membrane ruffling in cultured cells. It is becoming apparent that quantitative information describing these types of cell movement is needed to study and understand better the processes of cell motility.…”
mentioning
confidence: 99%